HBR's 10 must reads on managing across cultures. - HBR (Boston Harvard Business Review Press, 2016)
If you read nothing else on managing across cultures, read these 10 articles. We?ve combed through hundreds of Harvard Business Review articles and selected the most important ones to help you manage culturally diverse employees, whether they?re dispersed around the world or you?re working with a multicultural team in a single location.
Includes index.
Keywords: International business enterprises--Personnel management